Exploring moral quandaries: An interpretative phenomenological inquiry into the ethical dilemmas faced by Emergency Medical Technicians (EMTs) in the Southern Philippines - Raifa M. Guro; Asnorah P. Hadji Ali; Ashley A. Bangcola; Monalinda M. Macawadib; Norhanie A. Ali; Alibasher D. Macalnas (Journal of Healthcare Administration, 2024)
Background: Emergency Medical Technicians (EMTs) in Lanao del Sur, Philippines, face ethical dilemmas shaped by the Meranao cultural value of ‘Maratabat,’ which emphasizes family honor and dignity. Understanding these cultural nuances is crucial for improving emergency medical care and addressing the ethical challenges encountered by EMTs in this region.